The Influence of The Level of Credit Risk and Liquidity Risk on Profitability in Banking Listed on The Bei for the 2018-2021 Period - Permata, Sri Utami; Halisa, Nur; Hendra Halim (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
The type of research used is descriptive quantitative, the type of data used is secondary data obtained from financial report data, research location via the official website of the Indonesia Stock Exchange (www. Idx.id). The population and sample in this research are banking companies with a sample size of 35 banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The research results show that Non Performing loans (NPL) have a negative and significant effect on Return On Assets (ROA) with a t-value < t-table. Loan to Deposit Ratio (LDR) has a significant effect on Return On Assets (ROA) with t-count > t-table. Simultaneous research results show that Non Performing Loans, Loan to Deposit Ratio to Return On Assets with a significant value is smaller than the standard value, the calculated f value is > f fable. The influence of the level of credit risk and liquidity risk on profitability in banks listed on the Indonesian Stock Exchange (BEI) for the 2018-2021 period is 28.2%.